The Implications of Logistics Service Quality, Logistics Tariff, and Advanced Technology on the Courier Logistics Performance PT Satria Antaran Prima Tbk with Customer Satisfaction as a Mediating Variable - Agastya Pramadya; Melia Eka Lestiani; Erna Mulyati (Siber Journal of Transportation and Logistics, 2026)
PT Satria Antaran Prima Tbk experienced a 6.59% decline in Gross Operating Profit (GOP) in 2024 despite a 9.7% increase in revenue, accompanied by customer complaints on social media. This condition indicates potential issues related to courier logistics performance and customer satisfaction associated with logistics service quality, tariffs, and technology utilization. This study aims to examine the effects of Logistics Service Quality, Logistics Tariff, and Advanced Technology on Customer Satisfaction and Courier Logistics Performance. Using a quantitative approach with PLS-SEM analysis, data were collected from 392 active customers in Jakarta. The findings reveal that Logistics Service Quality, Logistics Tariff, and Advanced Technology positively and significantly influence Customer Satisfaction. Furthermore, Customer Satisfaction significantly improves Courier Logistics Performance and mediates the relationship between the independent variables and Courier Logistics Performance. These findings highlight the importance of service quality, competitive pricing, and technological advancement in enhancing customer satisfaction and logistics performance.